First Amendment Celebration Dec. 6 to be broadcast live - Fresno State::::::::: (2013)
The First Amendment Celebration 8:30 a.m.-3 p.m. Friday, Dec. 6, at Fresno State will be broadcast live on Comcast Channel 94 and AT&T U-verse Channel 99 and streamed live.